Difficulties in diagnosis of primary AL-amyloidosis - V. A. Khyshova; I. G. Rekhtina; M. V. Firsova; L. P. Mendeleeva (Онкогематология, 2021)
Objective of the study: analysis of AL-amyloidosis (AL-A) diagnostics in real clinical practice and to determine the main approaches for the earlier detection of this disease.Materials and methods. A retrospective analysis of medical records of 34 patients with newly diagnosed AL-A.Results. The median time from first symptoms appearance to the diagnosis was more than 2 years. Most often, the pathological process in AL-A involves the kidneys, heart and gastrointestinal tract; moreover, at the time of diagnosis, most patients already have an injury of 2 or more organs. In half of the patients, a biopsy of the damaging organ was performed to verify the diagnosis; according to our data, histological examination of “easily accessible” locus not less informative. Symptoms characteristic of amyloidosis, such as periorbital purpura or macroglossia, are observed in a small part of patients and refer to late manifestations of the disease.Conclusion. The versatility of AL-A manifestations leads to a late diagnosis, which affects overall survival. The main signs were highlighted that should alert doctors in relation to this pathology.